2017
DOI: 10.1093/mnras/stx1765
|View full text |Cite
|
Sign up to set email alerts
|

Interpreting the star formation efficiency of nearby molecular clouds with ionizing radiation

Abstract: We investigate the origin of observed local star formation relations using radiative magnetohydrodynamic simulations with self-consistent star formation and ionising radiation. We compare these clouds to the density distributions of local star-forming clouds and find that the most diffuse simulated clouds match the observed clouds relatively well. We then compute both observationally-motivated and theoretically-motivated star formation efficiencies (SFEs) for these simulated clouds. By including ionising radia… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
81
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(98 citation statements)
references
References 71 publications
16
81
0
1
Order By: Relevance
“…This order of magnitude is in line with observations in the Galaxy (Lada & Lada 2003). It also agrees with the simulation by Geen et al (2017), labelled 'L', which has a similar initial mass and surface density, and includes ionization feedback - Geen et al (2017) found that the SFE for that cloud was closer to observations of local star-forming regions compared to denser models, where SFEs approached 100 per cent.…”
Section: Bulk Grid Propertiessupporting
confidence: 88%
“…This order of magnitude is in line with observations in the Galaxy (Lada & Lada 2003). It also agrees with the simulation by Geen et al (2017), labelled 'L', which has a similar initial mass and surface density, and includes ionization feedback - Geen et al (2017) found that the SFE for that cloud was closer to observations of local star-forming regions compared to denser models, where SFEs approached 100 per cent.…”
Section: Bulk Grid Propertiessupporting
confidence: 88%
“…There is no clear theoretical link between the SFE and projected column density, although Clark & Glover (2014) argue that there may be a link between the observed column density and the local density around the star. Geen et al (2017) reproduce the SFE observed by Lada et al (2010), although they find that the result is likely to be dependent on the average density of the neutral gas in the cloud. These simulations produce similar results to the simulations of Colin et al (2013).…”
Section: The Imf and Sfe Of Molecular Cloudsmentioning
confidence: 78%
“…The initial density profile is perturbed with a turbulent velocity field, analogously to the set up used in Geen et al (2017). The initial turbulence of the clouds follows a Kolmogorov power spectrum with random phases and has an amplitude such that the cloud is approximately in virial equilibrium.…”
Section: Initial Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, some fraction of cold gas can be converted into star clusters, although the conversion efficiency is not understood well (e.g., Geen et al 2017). Therefore, our results suggest that stellar distribution can sensitively depend on the metallicity of galaxies.…”
Section: Metallicity Dependencementioning
confidence: 78%